1994
DOI: 10.1523/jneurosci.14-03-01555.1994
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of the shell of the nucleus accumbens in oral behavior of freely moving rats

Abstract: Behavioraleffects of intra-accumbens administration of the dopamine DA, receptor agonist (3,4-dihydroxyphenylimino)-2-imidazoline (DPI) were studied in freely moving rats. Three distinct areas were examined: core, shell and "shore," namely, the border region of the core and shell. DPI (5 pg) administered into the shell, but not areas ventral to the shell, increased chewing, tongue protrusion, sniffing, and grooming; it also induced abnormal oral behavior, namely, largeamplitude chewing.A similar dose of DPI ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 27 publications
2
39
1
1
Order By: Relevance
“…The outcome of the present study confirms the earlier reported finding that the shell, but not the core, of the nucleus accumbens is involved in the control of oral behaviour, especially jaw movements (Borcli et al, 1989;Cools et al, 1993;Prinssen et al, 1994): the combined administration of SKF 82985 and quinpiroie was only effective when injected into the shell, but not the core, of the nucleus accumbens. The finding that especially the shell of the nucleus accumbens is in volved in oral behaviour is understandable in view of the fact that the shell projects to a part of the ventral pallidum, that is known to be involved in oral be haviour (Spooren et al, 1989).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The outcome of the present study confirms the earlier reported finding that the shell, but not the core, of the nucleus accumbens is involved in the control of oral behaviour, especially jaw movements (Borcli et al, 1989;Cools et al, 1993;Prinssen et al, 1994): the combined administration of SKF 82985 and quinpiroie was only effective when injected into the shell, but not the core, of the nucleus accumbens. The finding that especially the shell of the nucleus accumbens is in volved in oral behaviour is understandable in view of the fact that the shell projects to a part of the ventral pallidum, that is known to be involved in oral be haviour (Spooren et al, 1989).…”
Section: Discussionsupporting
confidence: 92%
“…The registration period lasted 240 min. Guide cannulas were implanted bilater ally into the shell or into the core of the nucleus accumbens according to previously described proce dures (Prinssen et al, 1994). The coordinates based on the atlas of Paxinos and Watson (1986) were: anterior = 10.6 mm, lateral = 0.5 mm, vertical = 8.0 mm (shell); anterior = 10.6 mm, lateral = 1.2 mm, ventral = 7.0 m m (core).…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…effects (cf. [22]) rather than to a lack of effect of ¿/-sulpiride, which ncmsignificantly attenuated all these oral behaviors (data not shown).…”
Section: Statisi It* Til Arta I Vs Is )mentioning
confidence: 87%
“…The procedure is described elsewhere in detail [22]. After sur gery the rats were housed individually in the original stockroom and allowed recovery from operation for at least 1 week.…”
Section: Methodsmentioning
confidence: 99%